The dynamics of nutrition research in West Africa: Tracking the evidence - Diatta, Ampa Dogui; Diop, Loty; Salm, Leah; Touré, Mariama; Diatta, Dieynab; Verstraeten, Roosmarijn (International Food Policy Research Institute, 2021)
At a point where there is a strong need to make the best use of available resources in order to address multiple malnutrition burdens in low- and middleincome countries, there is a growing demand for evidence that can effectively inform decision-making (Ioannidis et al. 2014; Dobrow, Goel, Upshur 2004). There is, however, a rapidly increasing body of research literature on nutrition (Bastian, Glasziou, Chalmers 2010) which often uses highly technical language; the resulting information overload impedes the efforts of decisionmakers to distill what is relevant and applicable to their context (Dobrow, Goel, Upshur 2004). Obtaining systematically synthesized evidence (both quantitative and qualitative) on a regular basis enables them to make evidence-informed decisions and has the potential to improve and practice.